Discordant population histories of host and its parasite: A role for ecological permeability of extreme environment - Jirsová, Dagmar; Štefka, Jan; Jirků, Miloslav (PLoS One, 2017)
Biogeographical and ecological barriers strongly affect the course of micro-evolutionary processes in free living organisms. Here we assess the impact of a recently emerged barrier on populations of limnic fauna. Genetic diversity and population structure in a host-parasite system (Wenyonia virilis tapeworm, Synodontis schall catfish) are analyzed in the recently divided Turkana and Nile basins. The two basins, were repeatedly connected during the Holocene wet/dry climatic oscillations, following late Pleistocene dessication of the Turkana basin. Mitochondrial DNA sequences for cytochrome oxidase I gene (cox I) and a whole genome scanning method-amplified fragment length polymorphism (AFLP) were employed. A total of 347 cox I sequences (representing 209 haplotypes) and 716 AFLP fragments, as well as 120 cox I sequences (20 haplotypes) and 532 AFLP fragments were obtained from parasites and hosts, respectively. Although results indicate that host and parasite populations share some formative traits (bottlenecks, Nilotic origin), their population histories/patterns differ markedly. Mitochondrial analysis revealed that parasite populations evolve significantly faster and show remarkably higher genetic variability. Analyses of both markers confirmed that the parasites undergo lineage fission, forming new clusters specific for either freshwater or saline parts of Lake Turkana. In congruence with the geological history, these clusters apparently indicate multiple colonisations of Lake Turkana from the Nile. In contrast, the host population pattern indicates fusion of different colonisation waves. Although fish host populations remain connected, saline habitats in Lake Turkana (absent in the Nile), apparently pose a barrier to the gene flow in the parasite, possibly due to its multihost lifecycle, which involves freshwater annelids. Despite partially corroborating mitochondrial results, AFLP data was not sufficiently informative for analyzing populations with recently mixed biogeographic histories.
Keywords: cestodózy; Phylogeny; molekulární evoluce; proteiny červů; Cestoda; mitochondriální DNA; DNA, Mitochondrial; Fish Diseases; zvířata; Lakes; interakce hostitele a parazita; Catfishes; Host-Parasite Interactions; extrémní prostředí; Polymorphism, Genetic; jezera; sumci; polymorfismus genetický; slané vody; ekosystém; Keňa; Electron Transport Complex IV; Saline Waters; Ecosystem; respirační komplex IV; nemoci ryb; Evolution, Molecular; Animals; teoretické modely; Extreme Environments; fylogeneze; Models, Theoretical; Kenya; Haplotypes; haplotypy; Helminth Proteins; Cestode Infections